Exploring Undergraduate Research Projects Success Factors in Muni University, Uganda - Nicholas, Nkamwesiga; Phelix, Businge Mbabazi; Ritah, Nafuna (Interdisciplinary Journal of Education Research, 2021)
This paper presents the success factors for undergraduate research projects (URPs) at Muni University. The objectives of the study were to determine the relevant skills required for the success of URPs and investigate the roles of students, supervisors and faculty towards the success of URPs. The study used a crosssectional design to collect data from 70 third-year (final year) students who belonged to the two (2) faculties of science and technoscience. The participants were selected using the purposive sampling technique since they belonged to the section of the students’ population that had undergone the execution of the URPs. SPSS-v.21 program was used to determine the reliability of the research instrument and analyse the collected data using the frequencies, percentages and median of the parameters that formed the constructs of the study. The research instrument was reliable at Chronbach’s alpha 0.9038. Results showed that research environment, research management, personal effectiveness, communication, networking and teamwork skills are paramount to the success of URPs. The study also found out that the key stakeholders (students, supervisors and faculty) perform their roles throughout the project period. However, there is a need to have a mechanism for project tracking, filing complaints, and having URPs externally examined, among others.